The Exposure, Vulnerability, and Ability to Respond of Poor Households to Recurrent Floods in Mumbai - Patankar, Archana (World Bank, Washington, DC, 2015)
This paper examines poor households in the city of Mumbai and their exposure, vulnerability, and ability to respond to recurrent floods. The paper discusses policy implications for future adaptive capacity, resilience, and poverty alleviation. The study focuses particularly on the poor households, which tend to have greater exposure and vulnerability to floods and limited ability to respond given the constraints on physical and financial resources. The study seeks to understand the implications of the fact that poor households are more likely than non-poor households to be located in flood-prone areas. The study used the land use maps for the selected flood-prone areas to determine the extent and spread of poor and non-poor households and other types of assets and activities in areas with chronic and localized flooding. Primary data were obtained through detailed household surveys to understand the vulnerability and impacts of the extreme floods of July 2005, recurrent floods and the ability of households to respond and cope. The study examined the option of relocation to flood-free areas and identified factors that influence families’ decisions regarding relocation. The study finds that a significantly large proportion of poor households are located near areas with chronic and localized flooding. These households are either below the poverty line or have low incomes and reside in informal settlements or old and dilapidated structures. Future climate risks are likely to put greater burden on the poor and push them further into poverty unless well directed efforts are made to protect them.